Colostrum avoidance practice and associated factors among mothers of children aged less than six months in Bure District, Amhara Region, North West, Ethiopia: A community-based cross-sectional study. - Ayenew Mose; Merga Dheresa; Bezatu Mengistie; Biresaw Wassihun; Haimanot Abebe (PLoS ONE)
Introduction The World Health Organization and the United Nations International Children's Emergency Fund jointly recommend colostrum feeding immediately following delivery of the newborn. Colostrum avoidance is the practice of discarding colostrum at least once within the first three days after delivery of the newborn. Colostrum contains antibodies that protect the newborn against disease. Despite this fact, many Ethiopian mothers see colostrum feeding as a cause of neonatal morbidity and mortality, and they believe colostrum should be discarded to alleviate its effects. However, the cause of this misconception about colostrum is not well researched in Ethiopia, particularly in the study area. Objective To assess the prevalence of colostrum avoidance and associated factors among mothers of children aged less than six months in Bure district, Amhara Region, North West, Ethiopia. Methods A community-based cross-sectional study was conducted from March 1st to 30th, 2019 in Bure district. Structured questionnaires and face to face interviews were used to collect data from 621 study participants. Multistage sampling technique was used to select study participants. Data were entered into Epi Data version 4.2.0 and then exported to Statistical Package for the Social Sciences version 23. Bivariate and multivariate logistic regression analyses were performed to identify predictors of colostrum avoidance practice. Results Six hundred twenty-one (621) mothers of children aged less than six months participated. The prevalence of colostrum avoidance was 14.5% (95%CI; 11.5-17.4). The multivariate analysis indicated that home delivery [AOR = 3.350, (95%CI; 2.517-14.847)], giving birth through cesarean section [AOR = 3.368, (95%CI; 1.339-8.471)], no participation in an antenatal care group [AOR = 1.889, (95%CI; 1.144-3.533)], poor knowledge of mothers about colostrum [AOR = 3.44, (95%CI; 2.45-4.977)], and poor attitude of mothers towards colostrum [AOR = 3.053, (95%CI; 1.157-8.054)] were important predictors of colostrum avoidance practice. Conclusion and recommendations Home delivery, giving birth through cesarean section, no participation in an antenatal care group, poor knowledge of mothers about colostrum, and poor attitude of mothers towards colostrum were significantly associated with colostrum avoidance practice. Therefore, health care workers in the district should promote institutional delivery, reduce the magnitude of cesarean section, encourage pregnant mothers to participate in an antenatal care group, and enhance maternal awareness about the merits of colostrum feeding. Moreover, health educations for mothers to have a positive attitude towards colostrum are important recommendations to be taken to prevent the further practice of colostrum avoidance.